2023
DOI: 10.7759/cureus.40638
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Embolism of COVID-19: A Year of Reflection

Abstract: The coronavirus disease 2019 pandemic has brought about significant changes in the medical field. While primarily characterized as a respiratory syndrome, COVID-19 is also associated with vascular events, particularly thrombotic complications. These events can manifest as initial presentations or develop as complications during the course of the disease, predominantly driven by immune-mediated mechanisms. MethodsPatients with thrombotic complications followed in the post-COVID-19 thrombosis consult of 2021 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…Furthermore, diabetic patients infected with COVID-19 have a higher rate of admission to the ICU [ 5 ]. Studies also reported a higher rate of deep venous thromboembolism with the occurrence of pulmonary embolism [ 7 ] and a higher odds ratio of hospital mortality and cardiovascular injury [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, diabetic patients infected with COVID-19 have a higher rate of admission to the ICU [ 5 ]. Studies also reported a higher rate of deep venous thromboembolism with the occurrence of pulmonary embolism [ 7 ] and a higher odds ratio of hospital mortality and cardiovascular injury [ 1 ].…”
Section: Introductionmentioning
confidence: 99%